Local N environment in the dilute nitrides Ga(N, P), Ga(N, As), and Ga(N, Sb). Issue 4 (2nd April 2013) - Güngerich, M.; Sander, T.; Heiliger, C.; Czerner, M.; Klar, P. J.
Abstract We study the hydrostatic pressure response of the local environment of N in the ternary dilute nitride alloys, i.e., GaN0.021P0.979, GaN0.085As0.915, and GaN0.015Sb0.985 by Raman spectroscopy and density functional theory (DFT) of the local vibrational mode (LVM) of N. In all samples studied N is surrounded by four Ga atoms. To a first approximation the N vibrational mode can be described by the N‐atom vibrating in a rigid cage formed by the four Ga nearest neighbors. However, our careful experimental and theoretical analysis reveals that, despite the same nearest neighbor environment of N in the three dilute nitride hosts under study, distinct differences between the pressure dependence of the corresponding local N‐vibrational modes remain. These differences are rather due to the different chemical identities of the anions of the host than due to differences in N content and strain. Furthermore, it is shown that the LVM of N in the three alloys behaves differently under hydrostatic pressure than the optical extended phonon modes of zincblende GaN.